Flame-retardant nylon composite material and preparation method thereof

By using composite materials made from modified polyamide resin and hyperbranched polyesteramide, the problems of high flame retardancy, long-term stability, and electrical insulation in new energy vehicles and photovoltaic power generation components have been solved, resulting in high-performance flame-retardant nylon composite materials that meet the extreme requirements of new energy vehicles and photovoltaic inverters.

CN120818236APending Publication Date: 2025-10-21HUAIAN QI INNOVATION MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511054429.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing technologies struggle to simultaneously achieve high flame retardancy ratings, mechanical stability under long-term high-temperature environments, excellent electrical insulation, and interfacial bonding strength in key components of new energy vehicles and photovoltaic power generation. Traditional methods suffer from issues such as excessive addition of flame retardants affecting material performance, insufficient interfacial bonding, inadequate long-term heat resistance, and lack of functional synergy.

Method used

By employing a composite of modified polyamide resin, polyphenylphosphonic acid diphenyl sulfone ester, glass fiber, γ-aminopropyltriethoxysilane, and hyperbranched polyesteramide, a covalently bonded interface layer and a dense carbon layer are formed through a specific process. Combined with the synergistic effect of charge blocking of the hyperbranched polymer, the material achieves high flame retardancy, mechanical stability, and electrical insulation.

Benefits of technology

Achieving UL94 V-0 flame retardancy at a thickness of 0.8 mm, with no cracking at -40℃ and high performance retention after 120℃/2000 h, it meets the high-performance requirements of new energy vehicles and photovoltaic inverters, reduces the overall cost of components, and improves the qualification rate of material production lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818236A_ABST
    Figure CN120818236A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer composite materials, and discloses a flame-retardant nylon composite material and a preparation method thereof. The composite material is prepared from the following components in parts by weight: 60 to 85 parts of modified polyamide resin, 12 to 20 parts of polysulfonyldiphenyl phenyl phosphonate, 25 to 45 parts of glass fiber, 0.3 to 1 part of gamma-aminopropyltriethoxysilane, 0.5 to 3 parts of hyperbranched polyesteramide, 0.5 to 1.5 parts of polytetrafluoroethylene coated anti-dripping agent and a specific antioxidant. The core innovation lies in that the molecular chain stability is improved through the p-xylylenediamine end group modified polyamide, and the UL94 V-0 level flame retardance of the ultrathin wall (0.8 mm), the cracking resistance at the temperature of-40 DEG C and the high retention rate after long-term thermal aging at the temperature of 120 DEG C are achieved in combination with the synergistic effect of interface bridging of the silane pretreated glass fiber and the hyperbranched polymer. The preparation process adopts a segmented temperature control extrusion and downstream injection anti-dripping agent technology, so that the dispersity of the components is guaranteed. The material is suitable for a new energy automobile battery pack upper cover plate and a photovoltaic inverter shell, and the industrial problems of light weight, high insulation, long-acting sealing and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite materials, and specifically discloses a flame retardant nylon composite material and a preparation method thereof. Background Art

[0002] Flame-retardant nylon composites for high-voltage electrical systems and key photovoltaic power generation components in new energy vehicles (such as battery pack covers and inverter heat sink housings) must simultaneously meet multiple extreme performance requirements: a high flame retardancy rating (UL94 V-0 @ ≤ 1.0 mm) in ultra-thin wall conditions, mechanical stability in long-term high-temperature environments, excellent electrical insulation, and interfacial bonding strength. Conventional glass fiber-reinforced flame-retardant nylon faces a core dilemma: increasing the flame retardant content to improve flame retardancy, but high additions lead to poor melt flowability, reduced interfacial compatibility, and a sharp drop in impact strength. While relying solely on polyamide matrix modification can improve processability, it struggles to balance thin-wall flame retardancy with long-term heat aging performance.

[0003] The current mainstream technology route has significant limitations:

[0004] Halogen-free flame retardant system defects: Hypophosphite flame retardants easily cause hydrolysis and aging of materials, leading to degradation of electrical properties in high temperature and high humidity environments. Although phosphorus-nitrogen compound systems are more environmentally friendly, they require an addition level of >25% to meet the V-0 rating, severely sacrificing mechanical properties.

[0005] Interface reinforcement bottleneck: Conventional silane coupling agents are prone to premature hydrolysis and failure during high-temperature mixing, resulting in insufficient interfacial bonding between glass fiber and resin, causing delamination and cracking of the material when impacted at -40°C.

[0006] Insufficient long-term heat resistance: When the polyamide end groups are not blocked, the residual carboxyl groups continue to catalyze oxidation above 120°C, causing molecular chain breakage. The tensile strength retention rate after 2000 hours of heat aging is often less than 70%;

[0007] Lack of functional synergy: Existing technologies mostly use a single modification method (such as only flame retardant or only toughening), which does not solve the repulsive effect between flame retardants and reinforcing phases, resulting in the inability to simultaneously improve the glow-wire ignition temperature (GWFI) and CTI value.

[0008] In addition, high-end application scenarios pose new challenges to materials: new energy vehicle battery packs need to pass 20G mechanical impact certification, requiring the material to have both high rigidity (≥160 MPa) and low-temperature toughness; photovoltaic inverter housings need to withstand a continuous operating temperature of 120°C while meeting the high-contrast requirements of laser marking, and traditional materials cannot take into account the above performance.

[0009] Therefore, it is urgent to develop new flame-retardant nylon composite materials that can simultaneously achieve 160 MPa-level high strength, -40°C crack-free toughness, and a performance retention rate of >85% after thermal aging at 120°C / 2000 h while ensuring UL94 V-0 level (0.8 mm) flame retardancy, so as to meet the extreme requirements of key component materials in the new energy and photovoltaic fields. Summary of the Invention

[0010] To solve the above-mentioned problems in the prior art, the present invention discloses a flame retardant nylon composite material and a preparation method thereof.

[0011] To achieve the above objectives, the present invention includes the following technical solutions.

[0012] A flame retardant nylon composite material is composed of the following raw materials in parts by weight:

[0013] 60-85 parts of modified polyamide resin,

[0014] 12-20 parts of polyphenylphosphonic acid diphenyl sulfone,

[0015] 25-45 parts of glass fiber,

[0016] γ-aminopropyltriethoxysilane 0.3-1 part,

[0017] 0.5-3 parts of hyperbranched polyester amide,

[0018] Anti-dripping agent: polytetrafluoroethylene coated type 0.5-1.5 parts,

[0019] Antioxidant: 0.2-1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0020] The preparation method of the modified polyamide resin is:

[0021] Polyamide 66 is placed in a vacuum drum reactor and dehydrated to a moisture content of ≤0.05%. After heating to 240-255°C, para-phenylenediamine is injected in an amount of 1.5-3.5% of the polyamide mass. The reaction is carried out for 2-4 hours under a vacuum of 0.09-0.1 MPa and nitrogen protection. The reaction endpoint is controlled by the change in melt viscosity to meet Δη≥0.3 dL / g.

[0022] In the above scheme, the carboxyl groups of the polyamide are terminated with p-phenylenediamine (Δη≥0.3 dL / g) to inhibit thermal oxidative chain scission, and combined with the interface synergy of the two active components, in some embodiments, the unification of 0.8 mm ultra-thin V-0 flame retardancy and -40°C crack resistance is achieved.

[0023] Furthermore, in the aforementioned flame-retardant nylon composite material, the hyperbranched polyester amide has a molecular weight of 800-2000 g / mol, terminal groups are a mixture of hydroxyl and carboxyl groups, with the hydroxyl group ratio being ≥60%, and a degree of branching of 0.45-0.65. In this embodiment, the branched structure (with a hydroxyl group ratio of ≥60%) (with a branching degree of 0.45-0.65) enhances matrix toughness through physical entanglement, while the carboxyl groups participate in flame-retardant crosslinking. In some embodiments, impact strength is increased by 130%.

[0024] Furthermore, in the above-mentioned flame-retardant nylon composite material, the glass fiber is pretreated with γ-aminopropyltriethoxysilane, and the pretreatment process is:

[0025] Prepare γ-aminopropyltriethoxysilane into a 1-3wt% ethanol solution, spray it onto the surface of the glass fiber, and dry it at 90-110℃ for 10-20 minutes. The silane attachment amount is 0.2-0.8wt%.

[0026] In the above scheme, 1-3wt% silane ethanol solution is sprayed and then dried at 90-110℃ to form a covalent bond interface layer, which blocks the crack propagation path and solves the low-temperature delamination problem of the traditional glass fiber / resin interface.

[0027] Furthermore, in the aforementioned flame-retardant nylon composite material, the modified polyamide resin has an intrinsic viscosity of 2.8-3.5 dL / g, as measured using a m-cresol solution at 25°C. In the aforementioned embodiment, the 2.8-3.5 dL / g viscosity range ensures that the modified polyamide exhibits both high flowability (processability) and molecular chain entanglement density (mechanical properties), thereby preventing melt fracture during extrusion due to high viscosity.

[0028] Furthermore, the flame retardant nylon composite material meets the following performance indicators:

[0029] The glow-wire ignition temperature (GWFI) must be ≥850°C, the charge-blocking resistance (CTI) must be ≥575 V at a thickness of 1.6 mm, and the tensile strength must be ≥160 MPa. In this solution, the GWFI ≥850°C and CTI ≥575 V are derived from the synergistic effect of the phosphorus-sulfur flame retardant system and the charge blocking properties of the hyperbranched polymer, meeting the insulation safety standards for high-voltage components in electric vehicles.

[0030] The present invention also discloses a method for preparing a flame retardant nylon composite material, comprising the following steps:

[0031] (1) preparing modified polyamide resin;

[0032] (2) pre-treated glass fiber;

[0033] (3) premixing the modified polyamide resin, poly(phenyl phosphonate diphenyl sulfone), hyperbranched polyester amide, and antioxidant and adding the mixture to the main feed port of a twin-screw extruder;

[0034] (4) Pretreated glass fiber is added from the side feed port, and the anti-drip agent is injected downstream of the melting section;

[0035] (5) Extrusion granulation: The screw temperature is controlled in five zones, and the speed is 400±50 rpm.

[0036] In the above preparation scheme, the segmented process of premixing the main material + side-feeding glass fiber + downstream injection of anti-dripping agent prevents high-temperature decomposition of the flame retardant and breakage of the glass fiber, thereby ensuring the flame retardant efficiency of thin-walled products.

[0037] Furthermore, in the above preparation method, the injection position of the anti-dripping agent in step (4) is located 4-6 times the screw diameter downstream of the glass fiber addition point, and the screw in this area is configured with a weak shear combination block, and the kneading angle is ≤30 degrees;

[0038] In step (5), the temperatures of the five zones are 230°C, 240°C, 250°C, 255°C, and 245°C, respectively.

[0039] In the above preparation scheme, downstream injection of 4-6 times the screw diameter + weak shear block (≤30°) reduces PTFE fiberization damage, allowing the anti-dripping agent to be evenly dispersed into microspheres rather than fibers, thereby improving flame retardant stability.

[0040] The present invention also discloses the use of the aforementioned flame-retardant nylon composite material in the manufacture of upper covers for new energy vehicle battery packs. The covers exhibited no cracking during a -40°C low-temperature impact test and passed both a 20G mechanical impact and IP67 sealing test. In some embodiments, amino-terminated modification inhibits hydrolysis and synergistically strengthens the interface, enabling the material to pass both the -40°C impact and IP67 sealing tests, addressing the pain point of seal failure during hot and cold cycling of battery packs.

[0041] The present invention also discloses the use of the flame-retardant nylon composite material in the manufacture of heat dissipation housings for photovoltaic inverters. After 2000 hours of continuous operation at 120°C, the housing maintains a UL94 V-0 flame retardancy rating and a heat distortion temperature ≥ 210°C. In some embodiments, a combination of hyperbranched polymer free radical capture and a dense carbon layer for protection ensures that flame retardancy and heat distortion temperature remain unchanged after 120°C / 2000 hours, meeting the 25-year lifespan requirement for photovoltaic inverters.

[0042] Furthermore, in the above application, the contrast ratio of the laser marking on the surface of the heat dissipation housing prepared is ≥70%. The above technical solution can effectively replace the polluting ink printing process.

[0043] Compared with the prior art, the present invention has the following outstanding beneficial effects:

[0044] 1. Improved long-term heat resistance and electrical stability

[0045] Through a unique polyamide end-group modification process, the material still maintains more than 85% of its tensile strength after 2000 hours of continuous aging at 120°C, with a glow-wire ignition temperature (GWFI) as high as 875°C. The insulation performance (CTI ≥ 575 V) at a thickness of 1.6 mm meets the highest level 1A standard, ensuring a 20-year service life for high-voltage components in new energy vehicles.

[0046] 2. Low temperature crack resistance and high sealing performance

[0047] The material's notched impact strength reaches 14.3 kJ / m² under extreme conditions of -40°C. The injection-molded battery pack cover has passed 20G mechanical shock certification (simulated collision) and IP67 sealing test (no leakage after immersion in 1 m water depth for 30 minutes), completely solving the problem of battery pack sealing failure in high-altitude and cold regions.

[0048] 3. Ultra-thin wall high flame retardant breakthrough

[0049] It has passed UL94 V-0 certification (flame self-extinguishing time ≤ 3.3 s) at a thickness of 0.8 mm, which is 35% thinner than traditional materials, contributing to the lightweight design of battery packs; at the same time, the laser marking contrast is ≥ 70%, meeting the requirements of ink-free marking on photovoltaic shells.

[0050] 4. Mass production stability and cost optimization

[0051] The downstream injection process of the anti-drip agent allows the glass fiber to retain its complete reinforcement effect, increasing the material production line qualification rate to 98% and reducing the overall component cost by 32% (compared to traditional flame-retardant nylon solutions). BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Comparison of the first extinguishing time (t1) in the flame retardant performance test;

[0053] Figure 2 Comparison of notched impact strength at -40°C (kJ / m²);

[0054] Figure 3 Comparison of tensile strength retention after 2000 h of thermal aging. DETAILED DESCRIPTION

[0055] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0056] The following is a table of raw materials used in the examples.

[0057] Table 1 Example raw materials

[0058]

[0059] Glossary:

[0060] PA66

[0061] Polyamide 66 is a base resin raw material formed by the condensation of a diamine with 6 carbon atoms in the nylon main chain and a diacid with 6 carbon atoms.

[0062] PPSPP

[0063] Polyphenylphosphonate Diphenyl Sulfone Ester is a halogen-free flame retardant that catalyzes carbonization through the phosphorus-sulfur synergistic effect.

[0064] HBP-HY

[0065] Hyperbranched Polyesteramide (HPAM), an interfacial enhancer, has a molecular branched structure that improves matrix toughness and flame retardancy.

[0066] PTFE / SAN

[0067] Polytetrafluoroethylene / Styrene-Acrylonitrile copolymer coating and anti-dripping agent core structure prevent molten droplets from igniting. 1010

[0069] PentaerythritolTetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) is a hindered phenol antioxidant.

[0070] UL94

[0071] Plastic combustion performance grade standard (Underwriters Laboratories Standard 94), V-0 grade requirements: vertical combustion single flame extinguishing time ≤ 5 s, no ignition dripping.

[0072] GWFI

[0073] Glow-Wire Ignition Temperature (Glow-Wire Ignition Temperature) is the highest temperature at which a material does not ignite when exposed to a high-temperature glow-wire (≥850°C for certification).

[0074] CTI

[0075] The Comparative Tracking Index (CATI) measures a material's resistance to arc breakdown (≥575 V is the highest level, 1A).

[0076] IP67

[0077] Ingress Protection Rating: Dustproof (completely dustproof) Grade 6 + Waterproof (waterproof after immersion at a depth of 1m for 30 minutes).

[0078] L / D

[0079] Screw length / diameter ratio (Length / Diameter Ratio), a key parameter of twin-screw extruder, affects the material melting and dispersion efficiency.

[0080] Δη

[0081] Melt viscosity change (Delta Eta), endpoint criterion for modified polyamide reaction (Δη ≥ 0.3 dL / g indicates effective amino group blocking).

[0082] rpm

[0083] The screw speed unit (Revolutions Per Minute) controls the material residence time and shear intensity (400±50 rpm is the optimized value).

[0084] 20G mechanical shock

[0085] Acceleration tests simulating vehicle collisions (20 times the acceleration of gravity) are conducted to verify the battery pack cover’s ability to withstand instantaneous impacts.

[0086] HDT

[0087] Heat Deflection Temperature: The temperature at which the material deformation meets the standard under a load of 1.82 MPa (≥210°C).

[0088] Example 1

[0089] 1. A flame retardant nylon composite material, composed of the following raw materials in parts by weight:

[0090] 60 parts of modified polyamide resin,

[0091] 12 parts of polyphenylphosphonic acid diphenyl sulfone,

[0092] 25 parts of glass fiber,

[0093] γ-aminopropyltriethoxysilane 0.3 parts,

[0094] 0.5 parts of hyperbranched polyester amide,

[0095] 0.5 parts of polytetrafluoroethylene coated anti-dripping agent,

[0096] 0.2 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0097] 1) The preparation method of the modified polyamide resin is as follows:

[0098] Polyamide 66 was placed in a vacuum drum reactor and dehydrated to a moisture content of 0.03%. After heating to 240°C, p-phenylenediamine (1.5% of the polyamide mass) was injected and reacted for 2 hours under a vacuum of 0.09 MPa and nitrogen protection. The melt viscosity change at the end of the reaction was Δη = 0.32 dL / g.

[0099] The hyperbranched polyester amide has a molecular weight of 800 g / mol, a terminal hydroxyl group ratio of 65%, and a branching degree of 0.45;

[0100] 2) The glass fiber pretreatment process:

[0101] Prepare γ-aminopropyltriethoxysilane into a 1wt% ethanol solution, spray it onto the glass fiber surface, and dry it at 90℃ for 20 minutes. The silane attachment amount is 0.2wt%;

[0102] 3) The preparation method of the composite material includes:

[0103] (1) preparing a modified polyamide resin according to the above process;

[0104] (2) pretreating the glass fiber according to the above process;

[0105] (3) premixing the modified polyamide resin, poly(phenyl phosphonate diphenyl sulfone), hyperbranched polyester amide, and antioxidant and adding the mixture to the main feed port of a twin-screw extruder;

[0106] (4) Pretreated glass fiber is added from the side feed port, and the anti-drip agent is injected downstream of the melting section (the injection position is 4 times the screw diameter from the glass fiber addition point, and this area is equipped with a weak shear combination block with a kneading angle of 25°);

[0107] (5) Extrusion granulation: five-zone temperature: 230℃ / 240℃ / 250℃ / 255℃ / 245℃, rotation speed: 350 rpm.

[0108] Example 2

[0109] A flame retardant nylon composite material is composed of the following raw materials in parts by weight:

[0110] 70 parts of modified polyamide resin,

[0111] 16 parts of polyphenylphosphonic acid diphenyl sulfone ester,

[0112] 35 parts of glass fiber,

[0113] γ-aminopropyltriethoxysilane 0.6 parts,

[0114] 1.8 parts of hyperbranched polyester amide,

[0115] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0116] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0117] 1) The preparation method of the modified polyamide resin is:

[0118] Dehydrate to a water content of 0.04%, heat to 248°C, inject p-phenylenediamine (2.5%), and react under a vacuum of 0.095 MPa for 3 hours, with Δη = 0.38 dL / g;

[0119] The hyperbranched polyester amide has a molecular weight of 1400 g / mol, a terminal hydroxyl group ratio of 70%, and a branching degree of 0.55;

[0120] 2) Glass fiber pretreatment:

[0121] 3wt% silane ethanol solution, dried at 100℃ for 15 minutes, silane attachment amount 0.5wt%;

[0122] 3) The preparation method of the composite material includes (other details are the same as those in Example 1):

[0123] Step (4) The anti-dripping agent injection position is 5 times the screw diameter away from the glass fiber addition point (weak shear block kneading angle 28°);

[0124] Step (5) The temperature of the fifth zone is the same as that in Example 1, and the rotation speed is 400 rpm.

[0125] Example 3

[0126] A flame retardant nylon composite material is composed of the following raw materials in parts by weight:

[0127] 85 parts of modified polyamide resin,

[0128] 20 parts of polyphenylphosphonic acid diphenyl sulfone,

[0129] 45 parts of glass fiber,

[0130] 1 part of γ-aminopropyltriethoxysilane,

[0131] 3 parts of hyperbranched polyester amide,

[0132] 1.5 parts of polytetrafluoroethylene coated anti-dripping agent,

[0133] 1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0134] 1) The preparation method of the modified polyamide resin is:

[0135] Dehydrate to a water content of 0.05%, heat to 255°C, inject p-phenylenediamine (3.5%), and react under a vacuum of 0.1 MPa for 4 hours, with a Δη of 0.41 dL / g.

[0136] The hyperbranched polyester amide has a molecular weight of 2000 g / mol, a terminal hydroxyl group ratio of 75%, and a branching degree of 0.65;

[0137] 2) Glass fiber pretreatment:

[0138] 2wt% silane ethanol solution, dried at 110℃ for 10 minutes, silane attachment amount 0.8wt%;

[0139] 3) The preparation method of the composite material includes (other details are the same as those in Example 1):

[0140] Step (4) The anti-dripping agent injection position is 6 times the screw diameter away from the glass fiber addition point (weak shear block kneading angle is 30°);

[0141] Step (5) Rotation speed 450 rpm.

[0142] Comparative Example 1

[0143] A nylon composite material is composed of the following raw materials in parts by weight:

[0144] 70 parts of modified polyamide resin (same process as in Example 2),

[0145] 16 parts of polyphenylphosphonic acid diphenyl sulfone ester,

[0146] 35 parts of glass fiber (not pretreated with silane),

[0147] 1.8 parts of hyperbranched polyester amide,

[0148] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0149] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0150] (without γ-aminopropyltriethoxysilane)

[0151] The preparation method is the same as Example 2.

[0152] Comparative Example 2

[0153] A nylon composite material is composed of the following raw materials in parts by weight:

[0154] 70 parts of modified polyamide resin (same process as in Example 2),

[0155] 16 parts of polyphenylphosphonic acid diphenyl sulfone ester,

[0156] 35 parts of glass fiber (pretreated with γ-aminopropylsilane, same process as in Example 2),

[0157] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0158] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0159] (Does not contain hyperbranched polyester amide)

[0160] The preparation method is the same as Example 2.

[0161] Comparative Example 3

[0162] A nylon composite material is composed of the following raw materials in parts by weight:

[0163] 70 parts of unmodified polyamide 66 (intrinsic viscosity 2.5 dL / g),

[0164] 16 parts of polyphenylphosphonic acid diphenyl sulfone ester,

[0165] 35 parts of glass fiber (pretreated with γ-aminopropylsilane, same process as in Example 2),

[0166] γ-aminopropyltriethoxysilane 0.6 parts,

[0167] 1.8 parts of hyperbranched polyester amide,

[0168] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0169] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0170] (Polyamide is not modified with terminal amino groups)

[0171] The preparation method is the same as Example 2.

[0172] Comparative Example 4

[0173] A nylon composite material is composed of the following raw materials in parts by weight:

[0174] 70 parts of modified polyamide resin (same process as in Example 2),

[0175] 16 parts of aluminum hypophosphite (replacing polyphenylphosphonate diphenyl sulfone),

[0176] 35 parts of glass fiber (pretreated with γ-aminopropylsilane, same process as in Example 2),

[0177] γ-aminopropyltriethoxysilane 0.6 parts,

[0178] 1.8 parts of hyperbranched polyester amide,

[0179] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0180] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0181] The preparation method is the same as Example 2.

[0182] Comparative Example 5

[0183] A nylon composite material is composed of the following raw materials in parts by weight:

[0184] 70 parts of modified polyamide resin (same process as in Example 2),

[0185] 16 parts of polyphenylphosphonic acid diphenyl sulfone ester,

[0186] 35 parts of glass fiber (pretreated with γ-aminopropylsilane, same process as in Example 2),

[0187] γ-aminopropyltriethoxysilane 0.6 parts,

[0188] 1.8 parts of hyperbranched polyester amide,

[0189] 1.0 part of polytetrafluoroethylene coated anti-dripping agent,

[0190] 0.6 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0191] In the preparation method:

[0192] The anti-drip agent is added to the main feed port simultaneously with the main material (not injected downstream).

[0193] Test Example 1

[0194] Thin-wall flame retardant performance comparison experiment

[0195] Objective: To verify the impact of component synergy on UL94 V-0 rating

[0196] method:

[0197] Injection molding preparation of specimens (size 125 × 13 × t mm, t = 0.8 mm)

[0198] Vertical combustion test according to UL94 standard:

[0199] Flame height 20 mm, application time 10 s

[0200] Record the first extinguishing time (t1), the burning time after the second ignition (t2), and whether the dripping matter ignites the absorbent cotton.

[0201] The results are shown in Table 2 and Figure 1 :

[0202] Table 2: UL94 test results of 0.8 mm thin-walled specimens

[0203]

[0204] in conclusion:

[0205] Example 2 achieves V-0 level at 0.8 mm thickness, and its key mechanism is:

[0206] Pre-treating the glass fiber with γ-aminopropylsilane enhances interfacial bonding and blocks crack propagation during combustion. Hyperbranched polyester amide promotes carbonization of the melt, forming a dense carbon layer with poly(phenylphosphonic acid diphenyl sulfone) (a dense carbon layer can be seen upon cross-sectional observation (the thickness is significantly higher than that of the control example)).

[0207] The absence of any active ingredient (Comparative Examples 1-2) or unmodified PA (Comparative Example 3) resulted in flame retardant failure.

[0208] Test Example 2

[0209] Low temperature impact toughness verification

[0210] Purpose: To evaluate the material's crack resistance at -40°C

[0211] method:

[0212] Injection molding standard notched impact specimen (80×10×4 mm, notch depth 2 mm)

[0213] Low temperature impact test according to ISO 179-1:

[0214] The samples were pre-treated in a -40℃ environmental chamber for 24 h.

[0215] Pendulum energy 5.5 J, span 62 mm

[0216] Record impact strength and fracture morphology (observe interface stratification)

[0217] The results are shown in Table 3 and Figure 2 :

[0218] Table 3: Comparison of notched impact strength at -40°C

[0219]

[0220] From Table 3 we can conclude that:

[0221] The impact strength of Example 2 is increased by 130% compared with that of Comparative Example 1. Its core advantages are:

[0222] Double interface synergy: silane reinforces glass fiber / resin chemical bonding + hyperbranched polymer improves matrix toughness. Unmodified PA (Comparative Example 3) is catalytically depolymerized by the end carboxyl groups, and its brittleness is aggravated at low temperatures.

[0223] Test Example 3

[0224] Long-term thermal aging performance test

[0225] Purpose: To verify the material performance retention rate after 120℃ / 2000 h

[0226] method:

[0227] The sample was placed in a forced air oven at 120°C for 2000 h.

[0228] Test tensile strength retention according to ISO 527

[0229] CTI value determined according to IEC 60112 (1.6 mm thickness)

[0230] The results are shown in Table 4 and Figure 3 :

[0231] Table 4: Performance changes after 2000 h thermal aging

[0232]

[0233] From Table 4 we can conclude that:

[0234] The performance degradation of Example 2 is significantly lower than that of the control group, which may be attributed to:

[0235] End amino blocking inhibits thermal oxidation: the residual carboxyl content is reduced from 48 mmol / kg to 9 mmol / kg (titration method), and the hydroxyl groups of hyperbranched polyester amide capture free radicals, delaying the breakage of molecular chains.

[0236] Test Example 4

[0237] Laser marking performance verification

[0238] Purpose: To evaluate the clarity of markings on the surface of photovoltaic inverter housings

[0239] method:

[0240] Injection molding 100×100×2 mm flat specimen

[0241] Laser marking parameters:

[0242] Wavelength 1064 nm, power 20 W

[0243] Scanning speed 1000 mm / s, frequency 20 kHz

[0244] Use a colorimeter to measure the L* value (brightness) of the marking area and the background area

[0245] Contrast = (L 标 -L 背 ) / L 背 .

[0246] The results are shown in Table 5:

[0247] Table 5: Laser marking contrast

[0248]

[0249] in conclusion:

[0250] Example 2 meets the contrast ratio of ≥70%, and its advantages are as follows:

[0251] Compatibility of modified PA with flame retardants: The decomposition temperature of poly(phenylphosphonic acid diphenyl sulfone) is greater than 350°C, which avoids smoke generated by laser thermal decomposition, and hyperbranched polyester amide promotes uniform heat absorption of the matrix.

[0252] Test Example 5

[0253] IP67 sealing test

[0254] Purpose: To verify the sealing performance of the upper cover of the new energy vehicle battery pack

[0255] method:

[0256] Injection molding dimensions: 400×300×3 mm cover (including sealing groove structure)

[0257] Tested according to IP67 standards:

[0258] Water depth 1 m, immersion 30 min

[0259] Water absorption indicator (color-changing silica gel) is placed inside

[0260] Detection of silica gel moisture content after disassembly (Karl Fischer method)

[0261] The results are shown in Table 6.

[0262] Table 6: IP67 sealing test

[0263]

[0264] Comparative Example 1 had weak interface bonding (missing silane), resulting in microcracks after precooling at -40°C (interface microcracks were observed after the sealing test), leading to water seepage.

[0265] Test Example 6

[0266] Glow Wire Ignition Temperature (GWFI) Verification

[0267] Purpose: To test the material's ability to resist high temperature ignition

[0268] method:

[0269] Prepare the test specimen according to IEC 60695-2-13 (60×60×1.6 mm)

[0270] The heating wire was heated at 20°C / step, and each step was applied for 30 s.

[0271] Record the ignition temperature (flame duration > 5 s).

[0272] The results are shown in Table 7.

[0273] Table 7: Glow Wire Ignition Temperature (GWFI) Verification

[0274]

[0275] The mechanism is speculated to be that poly(phenylphosphonic acid diphenyl sulfone) decomposes at 650℃ to generate PO· free radicals, which quench the flame, and at the same time, hyperbranched polyester amide is cross-linked to form carbon.

[0276] Test data summary:

[0277] The core technical advantages of the flame-retardant nylon composite material of this invention are fully verified through six test cases:

[0278] Ultra-thin-wall flame retardant: 0.8 mm thickness passed UL94 V-0 certification (test case 1), breaking through the bottleneck of lightweight design of new energy vehicle battery packs;

[0279] Low-temperature crack resistance: -40°C notched impact strength reaches 14.3 kJ / m² (Test Case 2), eliminating the risk of battery pack cover cracking in cold regions.

[0280] Long-lasting heat resistance: Tensile strength retention after aging at 120°C / 2000 h is >89% (Test Example 3), ensuring a 20-year service life for the photovoltaic inverter housing.

[0281] High insulation safety: 1.6 mm thickness CTI ≥ 575 V (Test Case 3), meeting the insulation reliability requirements of high-voltage components in electric vehicles;

[0282] Sealing protection: IP67 test water seepage <100 ppm (Test Case 5), enabling inspection-free mass production of battery pack sealing covers;

[0283] Comprehensive cost reduction: The material qualification rate increased to 98% (comparison of test cases 4 / 5), reducing the overall component cost by 32% compared to traditional solutions.

[0284] The above are only a few preferred embodiments of the present invention, and their description is relatively specific and detailed, but it should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art may make various modifications and improvements without departing from the scope of the present invention, and such modifications and improvements are within the scope of protection of the present invention.

Claims

1. A flame retardant nylon composite material, characterized in that: It is composed of the following raw materials in parts by weight: 60-85 parts of modified polyamide resin, 12-20 parts of polyphenylphosphonic acid diphenyl sulfone, 25-45 parts of glass fiber, γ-aminopropyltriethoxysilane 0.3-1 part, 0.5-3 parts of hyperbranched polyester amide, Anti-dripping agent: polytetrafluoroethylene coated type 0.5-1.5 parts, Antioxidant: 0.2-1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; The preparation method of the modified polyamide resin is: Polyamide 66 is placed in a vacuum drum reactor and dehydrated to a moisture content of ≤0.05%. After heating to 240-255°C, para-phenylenediamine is injected in an amount of 1.5-3.5% of the polyamide mass. The reaction is carried out for 2-4 hours under a vacuum of 0.09-0.1 MPa and nitrogen protection. The reaction endpoint is controlled by the change in melt viscosity to meet Δη≥0.3 dL / g.

2. The flame retardant nylon composite material according to claim 1, characterized in that: The hyperbranched polyester amide has a molecular weight of 800-2000 g / mol, an end group of a mixture of hydroxyl and carboxyl groups, with the hydroxyl group accounting for ≥60%, and a branching degree of 0.45-0.

65.

3. The flame retardant nylon composite material according to claim 1, characterized in that: The glass fiber is pretreated with γ-aminopropyltriethoxysilane, and the pretreatment process is as follows: Prepare γ-aminopropyltriethoxysilane into a 1-3wt% ethanol solution, spray it onto the surface of the glass fiber, and dry it at 90-110℃ for 10-20 minutes. The silane attachment amount is 0.2-0.8wt%.

4. The flame retardant nylon composite material according to claim 1, characterized in that: The modified polyamide resin has an intrinsic viscosity of 2.8-3.5 dL / g, which is measured using a m-cresol solution at 25°C.

5. The flame retardant nylon composite material according to claim 1, characterized in that: Meet the following performance indicators: Glow wire ignition temperature GWFI ≥ 850℃, CTI ≥ 575 V at 1.6 mm thickness, tensile strength ≥ 160 MPa.

6. The method for preparing the flame-retardant nylon composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) preparing modified polyamide resin; (2) pre-treated glass fiber; (3) premixing the modified polyamide resin, poly(phenyl phosphonate diphenyl sulfone), hyperbranched polyester amide, and antioxidant and adding the mixture to the main feed port of a twin-screw extruder; (4) Pretreated glass fiber is added from the side feed port, and the anti-drip agent is injected downstream of the melting section; (5) Extrusion granulation: The screw temperature is controlled in five zones, and the speed is 400±50 rpm.

7. The preparation method according to claim 6, characterized in that In step (4), the anti-dripping agent injection position is located 4-6 times the screw diameter downstream of the glass fiber addition point, and the screw in this area is equipped with a weak shear combination block with a kneading angle of ≤30 degrees; In step (5), the temperatures of the five zones are 230°C, 240°C, 250°C, 255°C, and 245°C, respectively.

8. Use of the flame-retardant nylon composite material according to any one of claims 1 to 5 in preparing the upper cover of a new energy vehicle battery pack, characterized in that: The cover plate has no cracks in the -40°C low temperature impact test and passes the 20G mechanical impact + IP67 sealing test.

9. Use of the flame-retardant nylon composite material according to any one of claims 1 to 5 in preparing a heat dissipation housing of a photovoltaic inverter, characterized in that: After the shell continuously works at 120° C. for 2000 hours, the flame retardant grade remains UL94 V-0 and the heat deformation temperature is ≥210° C.

10. The use according to claim 9, characterized in that The laser marking contrast ratio of the surface of the prepared heat dissipation housing is ≥70%.